2013
DOI: 10.3109/08923973.2013.830125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium onPteridium aquilinumand urethane-induced lung carcinogenesis

Abstract: The results of our previous study demonstrated that ptaquiloside, the main toxic agent found in Pteridium aquilinum, suppresses natural killer (NK) cell-mediated cytotoxicity. However, the ability of ptaquiloside to suppress the cytotoxicity of NK cells was prevented by selenium supplementation. NK cells play an important role in the innate immune response and have the ability to kill tumor cells. Therefore, we hypothesized that selenium may prevent the higher susceptibility to urethane-induced lung carcinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…They play a major role in pulmonary inflammation and adenocarcinoma [27]. It has been well documented that the molecular mechanism of ethyl carbamateinduced lung cancer is based on integration of TNF signals with NF-кB that accelerate tumour progression [28]. Histological studies confirmed the biochemical results of the current work.…”
Section: Cells Cd11bsupporting
confidence: 78%
“…They play a major role in pulmonary inflammation and adenocarcinoma [27]. It has been well documented that the molecular mechanism of ethyl carbamateinduced lung cancer is based on integration of TNF signals with NF-кB that accelerate tumour progression [28]. Histological studies confirmed the biochemical results of the current work.…”
Section: Cells Cd11bsupporting
confidence: 78%
“…All the GO terms assigned to these genes were examined, and obtained by Fisher's exact test and x 2 test for calculating the level of significance as described [16,17].…”
Section: Go Analysismentioning
confidence: 99%
“…The results were in agreement with earlier studies that postulated urethane induce over expression of key molecules such as NF-κB, Stat3, pStat3; IL-1β, those play a major role in chronic inflammation and lung adenocarcinoma (Bernert et al, 2003 ). The molecular mechanism of urethane-induced lung cancer based on integration of TNF signals with NF-кB that accelerate tumor progression (Nakahara et al, 2013 ). Intratracheal inhalation of either GNPs or LGNPs showed non-significant difference in LDH, CEA and AFP in comparison to control group.…”
Section: Discussionmentioning
confidence: 99%